The rust transferred proteins—a new family of effector proteins exhibiting protease inhibitor function. (24th September 2012) - Pretsch, Klara; Kemen, Ariane; Kemen, Eric; Geiger, Matthias; Mendgen, Kurt; Voegele, Ralf
Summary Only few fungal effectors have been described to be delivered into the host cell during obligate biotrophic interactions. RTP1p, from the rust fungi Uromyces fabae and U. striatus, was the first fungal protein for which localization within the host cytoplasm could be demonstrated directly. We investigated the occurrence of RTP1 homologues in rust fungi and examined the structural and biochemical characteristics of the corresponding gene products. The analysis of 28 homologues showed that members of the RTP family are most likely to occur ubiquitously in rust fungi and to be specific to the order Pucciniales. Sequence analyses indicated that the structure of the RTPp effectors is bipartite, consisting of a variable N‐terminus and a conserved and structured C‐terminus. The characterization of Uf‐RTP1p mutants showed that four conserved cysteine residues sustain structural stability. Furthermore, the C‐terminal domain exhibits similarities to that of cysteine protease inhibitors, and it was shown that Uf‐RTP1p and Us‐RTP1p are able to inhibit proteolytic activity in Pichia pastoris culture supernatants. We conclude that the RTP1p homologues constitute a rust fungi‐specific family of modular effector proteins comprising an unstructured N‐terminal domain and a structured C‐terminal domain, which exhibit protease inhibitory activity possibly associated with effector function during biotrophic interactions.